The future utility of the instruments of planning law for sustainable settlement development - Runkel, Peter (Raumforschung und Raumordnung | Spatial Research and Planning, 1999)
Ensuring that the instruments of planning law are a suitable means of contributing to the aim of sustainable settlement development requires that these instruments should be revised and improved continuously to incorporate the merits of instruments which have proved their worth. The demands now being made of spatial planning and plan implementation and which need to be taken into account are explored from eight different perspectives. The instruments created by the 1998 Federal Regional Planning Act (ROG) are attested to have future utility; the author insists that it is now vital for the federal states in Germany to follow up on this initial step by showing an equal level of commitment in translating this legislative framework into concrete provisions in state planning legislation.
Keywords: Article